The art of creative thinking 89 ways to see things differently - Judkins, Rod (Perigee Books, 2016)
"An inspiration-sparking look at creativity, featuring brief examples of artists, writers, and innovators who have broken the mold. In succinct and engaging entries, Rod Judkins, a lecturer at the world-famous Central Saint Martin's College of Art, collects inspiring examples of creative thinkers throughout history, showing how we can all learn from them to improve our lives and our work. The Art of Creative Thinking presents an extraordinary array of examples, from the Dada Manifesto and Andy Warhol's Factory to the films of Ed Wood and the catwalks of Alexander McQueen, along with many others. Readers will learn about the most successful class in educational history (in which every student won a Nobel Prize), how frozen peas were invented, and why 95 percent of Apocalypse Now ended up on the cutting-room floor. Takeaways include: - Be stubborn about compromise. - Plan to have more accidents. - Be mature enough to be childish. - Contradict yourself more often"--Provided by publisher